Spiradiclis Spiradiclis hechiensis (Rubiaceae), a new cave-dwelling species from Northwest Guangxi, China - Xiong, Chi; Sun, Fu-Zhang; Yang, Yu-Xin; Wu, Lei (Phytotaxa, 2025)
A new species of Rubiaceae, Spiradiclis hechiensis, is described and illustrated from a cave in the Karst region of Northwest Guangxi, China. Morphologically, it is related to S. pauciflora in the shape and color of the corolla. It can be easily distinguished by the shape of leaf blades, bracts, and calyx lobes, the number of secondary veins and flowers, as well as the size of capsules and seeds. At present, only one population has been confirmed to have approximately 50–100 mature individuals from the type locality. According to the IUCN Red List Categories and Criteria, it is provisionally assessed as Critically Endangered [CR B1+2ab (iii)].